Analysis and Design of Customer Satisfaction Systems Against the Technicians from the Repair Service of Photocopy Machine At PT Copindo Renanta Using the SAW Method - Thessa Seftiani Dewi; Dram Renaldi (Tech-E, 2019)
For companies that work in the services sector, service quality is something very important to establish long-term relationships with its customers. At this time, PT Copindo Renanta evaluates the performance of technicians by provide a service satisfaction forms that made from a paper for the customer against the technician performance that can be manipulated by the technician so that the company cannot assess customer satisfaction with the true service of the technicians. The making of customer satisfaction system against the technicians from the repair service of photocopy machine at PT Copindo Renanta using the SAW method can provide an accurate and trusted results of technician performance calculations from photocopier repair services because calculations are carried out using the SAW method based on several values from the criteria by the customer filled. The system also supports a process of the order a copy machines repair services for customers who want to repair their machines (only need an internet connection and web browser to access and use anywhere and anytime needed, no need to wait for working hours), and support companies to make a technician performance assessment report till a repair photocopy machines transactions report.